2010
DOI: 10.1111/j.1600-0838.2010.01234.x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining educational differences in leisure‐time physical activity in Europe: the contribution of work‐related factors

Abstract: Although educational differences in leisure-time physical activity (LTPA) exist across Europe, the independent effect of educational level on leisure-time physical activity has rarely been explored. This study examines the relative contribution of occupational class, employment status, and educational level to LTPA across 12 European countries. The data were obtained from 12 European health surveys conducted at the turn of the century and identified in the EUROTHINE project. All information was self-reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 33 publications
7
27
0
3
Order By: Relevance
“…At the level of the individual. Mäkinen et al (12) previously found educational attainment to be the strongest determinant of leisure-time physical activity across 12 European countries. At the macrolevel, we show here that educational attainment (the percentage completing tertiary education) was also related to between-country differences in leisure-time physical activity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…At the level of the individual. Mäkinen et al (12) previously found educational attainment to be the strongest determinant of leisure-time physical activity across 12 European countries. At the macrolevel, we show here that educational attainment (the percentage completing tertiary education) was also related to between-country differences in leisure-time physical activity.…”
Section: Discussionmentioning
confidence: 97%
“…The mean age of included participants by country was not reported for any study, but in most cases, the uniform study design aimed to generate a sample of similar age profile in each countiy (1,4,10,13,19,20,29). In the study of Mäkinen et al (12), which involved data from 12 national health surveys, only adults age 30 to 59 yr were included. All analyses were conducted using Stata 11.1 (21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Health related behavior can be positively influenced only by addressing health-related behaviors and socioeconomic and environmental factors in PA policies. In various studies that present data from the European countries, it has been shown that smoking [5, 6], excessive alcohol consumption [7], lack of physical exercise [8, 9] and obesity [10] are all more common in lower socioeconomic groups. However, the extent of the impact of behavioral risk factors on health differs between countries.…”
Section: Introductionmentioning
confidence: 99%
“…Outra associação esperada na presente pesquisa era a maior prevalência de atividade física em sujeitos com maior escolaridade. Pesquisa realizada em doze países europeus mostrou que a atividade física no lazer foi diretamente associada com o alto nível de escolaridade dos sujeitos 29 . Outros achados também associaram positivamente maior nível de escolaridade com a prática de atividade física 21,24,30 .…”
Section: Introductionunclassified